Study on the effects of Massa Medicata Fermentata with different formulations on the intestinal microbiota and enzyme activities in mice with spleen deficiency constipation - Liang, Xuejuan; Wan, Dan; Li, Xinliang; Peng, Yanmei; Chen, Linglong (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectiveThis study aims to explore the therapeutic mechanism of Massa Medicata Fermentata (MMF) with different formulations on spleen deficiency constipation in mice by analyzing gastrointestinal hormones, D-xylose, intestinal microbiota, and intestinal enzyme activities.MethodsA spleen deficiency constipation model was established using an oral administration of Sennae Folium decoction combined with controlled diet and water intake. After successful model establishment, the mice with spleen deficiency constipation were treated with MMF S1, S2, S3. Following the intervention, serum samples from each group of mice were collected to measure VIP, 5-HT, and D-xylose. Additionally, small intestine contents were analyzed for intestinal enzyme activity and subjected to 16S rRNA high-throughput sequencing.ResultsMice with spleen deficiency constipation showed significant decreases in body weight and fecal water content. In contrast, the body weight of the CS2 and CS3 groups returned to normal levels, and fecal water content in the CS2 and CS3 groups also returned to normal. The MMF S2 and S3 significantly increased protease and sucrase enzymes levels compared with CM group. Serum D-xylose levels were significantly reduced in the CM and CS2 group. VIP levels increased significantly in the CM group but decreased in the CS2 and CS3 groups. Additionally, 5-HT levels in the CM and CS1 groups decreased significantly, with the CS2 group returning to normal and the CS3 group showing significant increases. 16S rRNA sequencing analysis revealed that all three MMF formulations effectively restored the intestinal microbiota composition in mice. LEfSe analysis identified characteristic microbiota linked to different intervention groups. The CS3 group significantly upregulated the chloroalkane and chloroalkene degradation and vibrio cholerae pathogenic cycle pathways compared to the CM group. Candidatus_Arthromitus in the CS3 group and Psychrobacter in the CS2 group were positive and negative correlations with 5-HT and VIP, respectively.ConclusionThe three formulations of MMF significantly alleviated spleen deficiency constipation symptoms by modulating intestinal enzyme activities, D-xylose, VIP, and 5-HT levels, and restoring intestinal microbiota balance. Psychrobacter and Candidatus_Arthromitus were identified as potential biomarkers for the treatment of spleen deficiency constipation. Different formulations of MMF have different mechanisms of regulating constipation through intestinal microbiota.